The Changing role of Civil Society in Nepal (Political Science Journal, 2024)
This paper delves into the dynamic landscape of civil society in Nepal, examining its pivotal role in shaping the trajectory of the country's democratic movement. Despite a relatively brief history compared to its South Asian counterparts, Nepal has witnessed a rapid proliferation of civil society organizations (CSOs) over the past five decades, fostering the emergence of an independent and influential civil society. From independent thinker's forums to media platforms and diverse interest groups, this study explores the multifaceted nature of civil society in Nepal. Organized into different key parts, the first part unfolds the historical perspective of civil society in Nepal, elucidating its meaning and evolution. The paper also navigates through the current spaces occupied by civil society and how these spaces have transformed over time. The last part of paper probes into the changing role of civil society, offering insights into its potential impact on governance. Throughout the analysis, the terms "civil society" and "civil society organizations" are used interchangeably, capturing the essence of their shared purpose in contributing to Nepal's socio-political landscape.